CURRENT ASPECTS OF COOPERATION BETWEEN UKRAINE AND NATO 2019–2022 - PRYDUN, Stepan (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Annotation. The article explores the main directions and outcomes of cooperation between Ukraine and NATO in the years 2019-2022, particularly in the context of heightened security challenges in Europe due to Russia's aggression against Ukraine. The dynamics of Ukraine-NATO relations are analyzed across political dialogue, practical collaboration, and integration perspectives. Priority areas and directions for the further development of partnership between Ukraine and NATO are identified, aiming at strengthening Ukraine's national security and its Euro-Atlantic integration.